Keys to Entrepreneurship: Integral Training of Entrepreneurs in University Scenarios - M, Gutiérrez L., José; H, Romero D., Carmen; María, Mesa; Olga, Novikova; César, Zapata-Molina; A, Romero, Pedro; Mariana, Bravo-Sepúlveda; H, Guerrero Latorre, Jorge (International Journal of Membrane Science and Technology, 2023)
Objective: To determine key factors that foster entrepreneurship among students at the University and thus lead to integral formation. Methodology: A descriptive, transactional study with a non-experimental design. The sample was non-probabilistic of 95 startup entrepreneurs who started an enterprise while studying at a state University in Colombia. A survey with 23 questions was applied to the entrepreneurs and SPSS software was used for data analysis. Results: The research revealed three key factors that sustain entrepreneurship among students: motivation to generate higher income and thus achieve self-fulfillment, work experience of a startup entrepreneur, and the drive for progressive sales growth. Conclusions: The most important factors that have determined the emergence and sustainability of startup entrepreneurship among university students are as follows: a) motivation to generate higher income and thus achieve self-fulfillment; b) work experience as an employee before starting a business, c) the drive for progressive sales growth. Originality: The issue that most affects the permanence of enterprises and a key factor for future entrepreneurs have been clarified, which is represented by university formation in both management and financial areas, to address the problem related to government policies.